Dirāsah fi Barnāmij al-Tamkīn li Qism Ta’līm al-Lugah al-‘Arabiyyah Kulliyyah al-Tarbiyyah al-Jāmi’ah al-Islāmiyyah al-Ḥukūmiyyah bi Madinah Pekalongan Sanah 2015-2019 - Moh. Sugeng Solehuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
The condition of economic, social and politics of this country brings great influence to many aspects of life including the policies in educational institution especially in Arabic Education Program. It becomes the controversial discourse in this decade. This article aims to describe the policies taken by the head of Arabic Education Program at Tarbiyah department (Islamic Education Study Program), STAIN Pekalongan. In the implementation, all of the policies should be done well, so that they can be used to solve problems. If a policy cannot be used to solve problems, then it is called as a failed policy. Therefore, to achieve the policy objectives, it needs the contribution of many people including the students, the staffs, the lecturers, and also the officials of the college.